PKM Malaysia Enhances Information Technology Innovation Outcomes for Higher Education Cooperatives - Lucy Chairoel; Afdaleni; Zulfariati; Zaiyar; Gusmulyani; AL; Yulia Setiani; Mirfaturiqa; Fauziah Zainin (Journal of Community Service and Application of Science, 2025)
The Community Service Program (PKM) implemented in Malaysia has opened up opportunities for international collaboration in developing information technology (IT) innovations to support the digital transformation of cooperatives in higher education settings. This activity underscored the importance of adapting technology to cooperative management systems to enhance efficiency, transparency, and accountability. Through a pilot study of digital cooperative models such as ANGKASA in Malaysia, participants gained insights into the implementation of integrated application-based information systems, the use of big data in membership management, and the optimization of digital platforms for financial reporting. The results of this activity demonstrated that the adoption of IT technology in Indonesian higher education cooperatives can strengthen institutional competitiveness, accelerate service processes, and increase active member participation. This PKM also reflects that the synergy between technological innovation and higher education-based cooperative governance is a strategic step towards modern and competitive cooperatives in the ASEAN digital era.